2020
DOI: 10.2147/idr.s241648
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Efficacy and Cost-Effectiveness of β-Lactam/β-Lactamase Inhibitor Combinations and Carbapenems in Liver Cirrhosis Patients with Gram-Negative Bacteria Bloodstream Infection</p>

Abstract: Background: Gram-negative bacteria bloodstream infection (GNB-BSI) results in considerable mortality and hospitality costs in cirrhotic patients. β-lactam/β-lactamase inhibitor combinations (BLBLIs) and carbapenems (CARs) are widely recommended for treating GNB-BSI in cirrhotic patients, while the efficacy and cost-effectiveness of two strategies have never been evaluated. Therefore, we conducted a retrospective cohort study to evaluate the efficacy and the cost-effectiveness of BLBLIs and CARs. Patients and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Some studies have suggested that BLBLIs are not inferior to carbapenems, 41 and may be cost-effective. 42 However, these studies rarely involve hospital acquired infections and BSI. A previous randomized clinical trial 43 did not support piperacillin-tazobactam as an alternative to meropenem in the treatment of ceftriaxone resistant Escherichia coli and KP bloodstream infections.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that BLBLIs are not inferior to carbapenems, 41 and may be cost-effective. 42 However, these studies rarely involve hospital acquired infections and BSI. A previous randomized clinical trial 43 did not support piperacillin-tazobactam as an alternative to meropenem in the treatment of ceftriaxone resistant Escherichia coli and KP bloodstream infections.…”
Section: Discussionmentioning
confidence: 99%